2009
DOI: 10.2353/ajpath.2009.080942
|View full text |Cite
|
Sign up to set email alerts
|

α5β1 Integrin Blockade Inhibits Lymphangiogenesis in Airway Inflammation

Abstract: The integrin ␣5␤1 has been previously implicated in tumor angiogenesis, but its role in the remodeling of both blood vessels and lymphatics during inflammation is at an early stage of understanding. We examined this issue using a selective, small-molecule inhibitor of ␣5␤1 integrin, 2-aroylamino-3-{4-[(pyridin-2-ylaminomethyl)heterocyclyl]phenyl}propionic acid (JSM8757), in a model of sustained airway inflammation in mice with Mycoplasma pulmonis infection, which is known to be accompanied by robust blood vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 56 publications
3
36
1
Order By: Relevance
“…For example, 51 integrin has been implicated in tumor angiogenesis (Taverna and Hynes, 2001) and has been found to be upregulated in vivo in a cerebral hypoxia model (Milner et al, 2008). In addition, developmental lymphangiogenesis seems to be unaffected, in contrast to a recent study showing that 51 blockade affects pathological lymphangiogenesis (Okazaki et al, 2009). Therefore, it would be interesting to test the role of endothelial 5 integrin in pathological models of angiogenesis, in order to validate endothelial cells as targets for the blocking reagents in those models.…”
Section: Implications For the Inhibition Of Angiogenesiscontrasting
confidence: 42%
“…For example, 51 integrin has been implicated in tumor angiogenesis (Taverna and Hynes, 2001) and has been found to be upregulated in vivo in a cerebral hypoxia model (Milner et al, 2008). In addition, developmental lymphangiogenesis seems to be unaffected, in contrast to a recent study showing that 51 blockade affects pathological lymphangiogenesis (Okazaki et al, 2009). Therefore, it would be interesting to test the role of endothelial 5 integrin in pathological models of angiogenesis, in order to validate endothelial cells as targets for the blocking reagents in those models.…”
Section: Implications For the Inhibition Of Angiogenesiscontrasting
confidence: 42%
“…It has also been shown that ␣9 integrin binds VEGF-C directly (13). Moreover, inhibition of ␣5␤1 integrin reduced lymphangiogenesis in inflamed airways after Mycoplasma pulmonis infection and in corneal inflammation (14,15). Recent papers also suggest that VEGFR-3 forms complexes with integrins, such as ␤1 and ␣5 in lymphatic endothelial cells (LEC) (16,17).…”
mentioning
confidence: 99%
“…S2). This process is regulated by several factors including integrins (9)(10)(11)(12)(13). In this study, we found that α9-mediated signaling is dispensable for CFA-induced lymphangiogenesis (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Factors, including vascular endothelial growth factor receptor 3 (VEGFR3), lymphatic vessel endothelial hyaluronan receptor 1 (LYVE-1), transcription factor prox-1, and integrins, regulate lymphatic vessel growth and development (9)(10)(11)(12)(13). Among the integrins, α9 integrin (α9 hereafter) is critical for the development of lymphatic valves (14,15).…”
mentioning
confidence: 99%